KERUSAKAN DAN PERKUATAN STRUKTUR BETON BERTULANG - Isneini, Mohd. (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2009)
Concrete made with Portland cement has been a popular constructing material all over the worldfor the past 180 years or more. However, cement mortar and concrete have some disadvantagessuch as delayed hardening, low tensile strength, low chemical resistance, large drying shrinkage.To reduce these advantages, many attemps to use polymers have been made. One such attemps ispolymer-modified (or polymer cement) mortar or concrete, which is made by modifying ordinaryportland cement with polymer additives such as latexes, redispersible polymer powders, watersoluble polymer, liquid resin and monomers. In this paper will be introduced Types of damagesoccurred to Reinforced concrete structures, method of repaired and usage of polimer concrete asa material used for repairation. In Indonesia polymer concrete is not common yet to use asconcrete mass because the cost needed to produce it is still high, so usage polimer for repairing isa choice to make it popular as a contruction material.